Antioxidant Activities, Phenolic and Flavonoid Contents of Methanolic Extract of Stelechocarpus burahol Fruit and its Fractions - Herlina, Nur; Riyanto, Sugeng; Martono, Sudibyo; Rohman, Abdul (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Kepel or Stelechocarpus burahol is an exotic fruit originating from Java, Indonesia. This research was intended to evaluate the antioxidant activities of extracts and fractions of kepel fruit pulp (KFP) based on radical scavenging capability towards 2,2′-azinobis(3-ethylbenzo thiazoline-6-sulphonic acid) diammonium salt (ABTS) and 2,2′-diphenildiphenyl-1-picrylhydrazil radical (DPPH). In this study, the radical scavenging activities were also correlated with total phenolics and flavonoid contents. Among the evaluated samples, the ethyl acetate fraction exhibited the highest antiradical antioxidant activity towards ABTS radical with IC50 of 0.35 μg/ml, lower than that of vitamin C (as positive control). It also showed highest antiradical activity using DPPH based assay. Methanolic extract had total phenolic content of 58.28 ± 0.37% wt/wt gallic acid equivalent, higher than its fraction. Meanwhile the petroleum ether soluble fraction revealed flavonoid content (76.06 ± 11.9%) as rutin equivalent, among the extract and fractions evaluated. Based on coefficient (R2) values, phenolics and flavonoids contents contributed to 73.09% and 30.99%% towards antiradical scavenging activities, respectively. Dhaka Univ. J. Pharm. Sci. 17(2): 153-159, 2018 (December)